Energy expenditure estimation during official soccer matches - Coelho, D. B.; Coelho, L. G.; Mortimer, L. A.; Condessa, L. A.; Ferreira-Junior, J. B.; Borba, D. A.; Oliveira, B. M.; Bouzas-Marins, J. C.; Soares, D. D.; Silami-Garcia, E. (Brazilian Journal of Biomotricity, 2010)
Among the many parameters used to evaluate the intensity of a physical activity, the energy expenditure is considered within the principal ones. The purpose of the current research was to compare the energy expenditure estimation of soccer players in the Under-20 league (U-20) with results of professional soccer players described in the literature. Eleven soccer players from the first-division Brazilian soccer were evaluated in 12 matches of an official championship. The relationship between HR and oxygen uptake was established in a laboratory. Right after such procedures, the energy expenditure was calculated from the VO2 rates that were found by an equation of linear regression, which were subsequently substituted by the rates given in kilocalories. The energy expenditure of a soccer match was estimated as 17.11 ± 1.45 kcal.min-1 or 13.1 ± 1.68 METs, which corresponded to a total average expenditure of 1539.86 ± 130.07 kcal during a complete match. Therefore, the conclusion is that soccer players of an Under-20 category present high values for energy expenditure during the matches of an official championship.